Design and Optimization of Febuxostat-loaded Nano Lipid Carriers Using Full Factorial Design - BHATT, Shailendra (Turk J Pharm Sci, 2021)
OBJECTIVES: This work aims to develop nanostructured lipid carriers (NLCs) to improve the oral bioavailability of febuxostat (FEB). MATERIALS AND METHODS: High shear homogenization, a well-known technique, followed by bath sonication with slight modifications was used to prepare FEB-loaded NLCs using oleic acid as liquid lipid and stearic acid as solid lipid. A total of 3² full factorial design was utilized to examine the effect of 2 independent variables, namely, X1 (liquid to solid lipid ratio) and X2 (surfactant concentration) on the Y1 (particle size) and Y2 (% entrapment efficiency) of the drug. The prepared NLCs were evaluated for particle size, polydispersity index, zeta potential, and (%) entrapment efficiency. RESULTS: The drug’s highest solubility was found in the stearic (solid lipid) and oleic acid (liquid lipid), which were further chosen for NLC preparation. Result of the present study showed an increase in entrapment efficiency and a decrease in particle size with the increase in liquid lipid to solid lipid ratio. With increased surfactant concentration, a small particle size is observed. The optimized formulation’s particle size and (%) entrapment efficiency was found to be 99 nm and 80%, respectively. The formulations’ zeta potential and polydispersity index were found within the range. Compared to plain drug suspension, the optimized formulation showed higher drug release, which may be due to the presence of the higher amount of liquid lipid. The particles shown in the transmission electron microscopy were round in shape and have smooth surface. Stability studies showed that the NLC formulation can be stored for a longer time period under room condition. CONCLUSION: FEB-loaded NLC were successfully prepared using full 3² factorial design, and can be further used for oral delivery of FEB for gout treatment.